A Mixture of Tocopherol Acetate and L-Menthol Synergistically Promotes Hair Growth in C57BL/6 Mice - Ahn, Seunghyun (Pharmaceutics, 2020)
Oral finasteride and topical minoxidil are single components approved by the US FDA for treating hair loss. Some other compounds originating from natural products are also traditionally used for promoting hair growth. In this study, observations of treated keratinocyte cells were used to demonstrate that tocopherol acetate, L-menthol, and stevioside exert an effect on cell regeneration. Furthermore, these were topically applied to the shaved skin of C57BL/6 mice to observe their effects on hair growth. A mixture of tocopherol acetate, L-menthol, and stevioside showed the highest potential for promoting hair growth in vivo. In in vivo experiments, the mixture of tocopherol acetate, L-menthol, and stevioside was more effective than tocopherol acetate or L-menthol alone in promoting hair growth. The transcriptome analysis of skin from the dorsal side of a mouse treated with tocopherol acetate or L-menthol versus vehicle revealed key changes in keratin, keratin-associated protein, forkhead box, sonic hedgehog, fibroblast growth factor 10, desmoglein 4, deoxyribonuclease 1-like 2, and cadherin 3, known to play roles in promoting hair growth.